Curcumin Mediated Gold Nanoparticles and Analysis of its Antioxidant, Anti-inflammatory, Antimicrobial Activity Against Oral Pathogens - Sreedevi Dharman; Gopal Maragathavalli; Rajeshkumar Shanmugam; Karpagavalli Shanmugasundaram (Association of Support to Oral Health Research (APESB), 2023)
Objective: To green synthesise gold nanoparticles using curcumin and to analyse its antioxidant, anti-inflammatory, and antimicrobial activity among oral pathogens. Material and Methods: Biosynthesised Curcumin Gold nanoparticles (CuAuNP) were evaluated by UV-visible spectrophotometer (UV-Vis), Transmission Electron Microscopy (TEM), and evaluation of antioxidant, anti-inflammatory and antibacterial activity against oral pathogens. Results: Synthesized CuAuNP were characterized using UV-visible spectrophotometry and showed peak absorption at 530nm. CuAuNp showed a 90.3% maximum scavenging ability of DPPH at a concentration of 50 μg/mL. CuAuNP exhibited 79.6 % of the highest anti-inflammatory activity at 50μg/mL than the standard drug diclofenac. TEM image clearly showed uniformly dispersed spherical-shaped gold nanoparticles with a size of about 20 nm. The biosynthesized nanoparticle was tested for its antimicrobial effect, and it showed a potent effect against S. aureus, E. faecalis, and C. albicans at 100µg/ mL. Enterococcus faecalis has a maximum zone of inhibition of 14 mm at 100µg/ mL of CuAuNp. Among gram-positive bacteria, a maximum zone of inhibition of 12 mm at 100µg/ mL was seen in S. aureus compared to S mutans. Candida albicans showed a maximum zone of inhibition of 18 mm at 25 μg/mL of CuAuNp. Conclusion: Curcumin-mediated gold nanoparticles with 20 nm size were effective and had strong antioxidant and anti-inflammatory activity at 50µg/ mL, antimicrobial action inhibiting microbes at 100µg/ mL concentration that can be used in treating various Oral mucosal lesions.